Knowledge and Creativity for a Sustainable World: the Universiti Sains Malaysia Approach - Campbell, James (INTI University College, 2010)
Sustainability is a critical aim of Malaysian public policy and an important aim in education. Nonetheless, what sustainability means as it relates to education and the relationship between education and a sustainable future is unclear. In this paper I shall investigate the role that Universities in Malaysia play in shifting the practice and culture of innovation and creativity towards more sustainable values and outcomes. Sustainable education is based on ensuring that the capacities of students and the broader society are reengaged and empowered through connecting education to the needs and aspirations of civil society and moving away from neo-liberal ideas of education as a practice of consumption towards, sustainable values of advancing human dignity. Creativity and innovation within such an educational framework are goals and practices deeply connected and embedded within sustainable commitments to social justice and the public good. As well as individual growth and development, which provide a critical legitimizing principle for university research and teaching. One of the key theoretical influences in making this argument is drawn from the arguments of Amartya Sen, whose theorization of capability may provide us with a way of thinking about social growth and development that is not possessively individualistic but rather socially concerned. I will discuss this in reference to the approach of University Sains Malaysia which provides an example of a public University seeking to engage sustainability and tie educational creativity and innovation back to the common good and a sustainable future. The philosophical aim of this paper is to show how universities can pursue creativity and innovation as socially useful practices for advancing humane and sustainable values throughout Malaysian society and avoid the fusion of creativity with possessive individualism, consumerization and social irresponsibility.